Westonci.ca makes finding answers easy, with a community of experts ready to provide you with the information you seek. Our platform provides a seamless experience for finding reliable answers from a knowledgeable network of professionals. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.
Sagot :
Certainly! Let's solve this problem step-by-step.
1. Finding [tex]\((f \cdot g)(x)\)[/tex]:
The expression [tex]\( (f \cdot g)(x) \)[/tex] represents the product of the functions [tex]\( f(x) \)[/tex] and [tex]\( g(x) \)[/tex].
[tex]\[ f(x) = 2x - 4 \][/tex]
[tex]\[ g(x) = x - 3 \][/tex]
Therefore,
[tex]\[ (f \cdot g)(x) = f(x) \cdot g(x) = (2x - 4)(x - 3) \][/tex]
To simplify this, we expand the product:
[tex]\[ (2x - 4)(x - 3) = 2x \cdot x + 2x \cdot (-3) - 4 \cdot x - 4 \cdot (-3) \][/tex]
[tex]\[ = 2x^2 - 6x - 4x + 12 \][/tex]
Combine like terms:
[tex]\[ = 2x^2 - 10x + 12 \][/tex]
So,
[tex]\[ (f \cdot g)(x) = 2x^2 - 10x + 12 \][/tex]
2. Finding [tex]\((f+g)(x)\)[/tex]:
The expression [tex]\( (f + g)(x) \)[/tex] represents the sum of the functions [tex]\( f(x) \)[/tex] and [tex]\( g(x) \)[/tex].
[tex]\[ f(x) = 2x - 4 \][/tex]
[tex]\[ g(x) = x - 3 \][/tex]
Therefore,
[tex]\[ (f + g)(x) = f(x) + g(x) = (2x - 4) + (x - 3) \][/tex]
To simplify this, combine like terms:
[tex]\[ = 2x + x - 4 - 3 \][/tex]
[tex]\[ = 3x - 7 \][/tex]
So,
[tex]\[ (f + g)(x) = 3x - 7 \][/tex]
3. Evaluating [tex]\((f - g)(1)\)[/tex]:
The expression [tex]\( (f - g)(x) \)[/tex] represents the difference of the functions [tex]\( f(x) \)[/tex] and [tex]\( g(x) \)[/tex].
So, we need to find [tex]\( (f - g)(1) \)[/tex]. First, let's find [tex]\( f(1) \)[/tex] and [tex]\( g(1) \)[/tex].
[tex]\[ f(x) = 2x - 4 \quad \text{so} \quad f(1) = 2(1) - 4 = 2 - 4 = -2 \][/tex]
[tex]\[ g(x) = x - 3 \quad \text{so} \quad g(1) = 1 - 3 = -2 \][/tex]
Therefore,
[tex]\[ (f - g)(1) = f(1) - g(1) = -2 - (-2) \][/tex]
Simplify the expression by subtracting a negative value:
[tex]\[ = -2 + 2 = 0 \][/tex]
So, the final results are:
[tex]\[ \begin{array}{c} (f \cdot g)(x)=2x^2 - 10x + 12 \\ (f+g)(x)=3x - 7 \\ (f-g)(1)=0 \end{array} \][/tex]
1. Finding [tex]\((f \cdot g)(x)\)[/tex]:
The expression [tex]\( (f \cdot g)(x) \)[/tex] represents the product of the functions [tex]\( f(x) \)[/tex] and [tex]\( g(x) \)[/tex].
[tex]\[ f(x) = 2x - 4 \][/tex]
[tex]\[ g(x) = x - 3 \][/tex]
Therefore,
[tex]\[ (f \cdot g)(x) = f(x) \cdot g(x) = (2x - 4)(x - 3) \][/tex]
To simplify this, we expand the product:
[tex]\[ (2x - 4)(x - 3) = 2x \cdot x + 2x \cdot (-3) - 4 \cdot x - 4 \cdot (-3) \][/tex]
[tex]\[ = 2x^2 - 6x - 4x + 12 \][/tex]
Combine like terms:
[tex]\[ = 2x^2 - 10x + 12 \][/tex]
So,
[tex]\[ (f \cdot g)(x) = 2x^2 - 10x + 12 \][/tex]
2. Finding [tex]\((f+g)(x)\)[/tex]:
The expression [tex]\( (f + g)(x) \)[/tex] represents the sum of the functions [tex]\( f(x) \)[/tex] and [tex]\( g(x) \)[/tex].
[tex]\[ f(x) = 2x - 4 \][/tex]
[tex]\[ g(x) = x - 3 \][/tex]
Therefore,
[tex]\[ (f + g)(x) = f(x) + g(x) = (2x - 4) + (x - 3) \][/tex]
To simplify this, combine like terms:
[tex]\[ = 2x + x - 4 - 3 \][/tex]
[tex]\[ = 3x - 7 \][/tex]
So,
[tex]\[ (f + g)(x) = 3x - 7 \][/tex]
3. Evaluating [tex]\((f - g)(1)\)[/tex]:
The expression [tex]\( (f - g)(x) \)[/tex] represents the difference of the functions [tex]\( f(x) \)[/tex] and [tex]\( g(x) \)[/tex].
So, we need to find [tex]\( (f - g)(1) \)[/tex]. First, let's find [tex]\( f(1) \)[/tex] and [tex]\( g(1) \)[/tex].
[tex]\[ f(x) = 2x - 4 \quad \text{so} \quad f(1) = 2(1) - 4 = 2 - 4 = -2 \][/tex]
[tex]\[ g(x) = x - 3 \quad \text{so} \quad g(1) = 1 - 3 = -2 \][/tex]
Therefore,
[tex]\[ (f - g)(1) = f(1) - g(1) = -2 - (-2) \][/tex]
Simplify the expression by subtracting a negative value:
[tex]\[ = -2 + 2 = 0 \][/tex]
So, the final results are:
[tex]\[ \begin{array}{c} (f \cdot g)(x)=2x^2 - 10x + 12 \\ (f+g)(x)=3x - 7 \\ (f-g)(1)=0 \end{array} \][/tex]
Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. Westonci.ca is your trusted source for answers. Visit us again to find more information on diverse topics.